수술 전 암 환자의 치료에 대한 태도, 공유의사결정, 불안이 항암치료 의사결정갈등에 미치는 영향 - 구남이(Koo, Nam Yee); 이지현(Lee, Ji Hyun) (Asian oncology nursing, 2017)
Purpose: This study was attempted to grasp the factors affecting the decision-making conflicts of preoperative cancer patients. Methods: The subjects of this study were 110 cancer patients scheduled to undergo surgeries at K university hospital. Data were collected utilizing scales for decision-making conflicts and anxiety state, and measurement tools for attitude toward treatment and, shared decision- making. Results: The level of decision-making conflicts over cancer treatment of preoperative cancer patients turned out to be slightly lower than the median. There were significant correlations between shared decision-making between physicians and patients, and quality of life which was a subdomain of attitude toward treatment. In multiple regression analysis, the most powerful predictor was the shared decision-making of physicians and patients. Overall, the explanatory power of the measured variables for decisionmaking conflicts about cancer therapy was 20%. Conclusion: The study highlights the importance of shared decision-making and quality of life which involves attitude toward treatment. Thereby, it is deemed to be necessary to develop intervention strategies regarding decision-making conflicts about cancer treatment in consideration of these variables. KCI Citation Count: 2